2018
DOI: 10.11607/jomi.6023
|View full text |Cite
|
Sign up to set email alerts
|

Retentive Properties of Two Stud Attachments with Polyetherketoneketone or Nylon Insert in Mandibular Implant Overdentures

Abstract: Within the limitations of this investigation, the attachment system with a PEKK insert indicated less abrasion and retention change than the attachment system with a nylon insert on both paralleled implants and axially tilted implants under 400,000 cyclic loadings and 1,080 insertion/removal cycles for 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 19 publications
3
59
0
1
Order By: Relevance
“…In the present study, CM LOC presented the most consistent retentive forces out of the three tested attachments, even in extreme implant angulations, and was affected by the latter only after a very high number of cycles. Previous studies on this attachment, although limited to slightly tilted implants, also confirmed the consistency of retentive forces (Choi et al, ; Passia et al, ). The initial retentive force varied substantially, with Group 0° presenting double the retentive force than the other groups.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the present study, CM LOC presented the most consistent retentive forces out of the three tested attachments, even in extreme implant angulations, and was affected by the latter only after a very high number of cycles. Previous studies on this attachment, although limited to slightly tilted implants, also confirmed the consistency of retentive forces (Choi et al, ; Passia et al, ). The initial retentive force varied substantially, with Group 0° presenting double the retentive force than the other groups.…”
Section: Discussionsupporting
confidence: 73%
“…A limited number of studies have examined one of the latest attachments (Choi, Yun, Jeong, & Huh, 2018;Passia, Ghazal, & Kern, 2016), while other newer attachment systems on the market have not yet been evaluated. To date, however, no studies have examined and compared the performance of the latest attachment systems.…”
mentioning
confidence: 99%
“…More retention loss was reported for a stud 2IOD compared to bar, ball and PEEK (polyether ether ketone) attachments in the presence of higher inter-implant angulations (Aroso et al, 2016;Choi, Yun, Jeong, & Huh, 2018;Kurtulus & Gurbulak, 2018;Srinivasan et al, 2016;Sultana, Bartlett, & Suleiman, 2017). Fatigue tests, simulating 5 years of denture function, did not produce wear in the metal stud abutments (Aroso et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…Based on in vitro and in vivo research, the effect of inter‐implant angulation on retention and wear of a stud retained 2IOD is inconclusive (ELsyad, Hatem, Shawky, & Emera, ; Jabbour et al, ; Kobayashi et al, ; Kurtulus & Gurbulak, ; Stephens, di Vitale, O'Sullivan, & McDonald, ). More retention loss was reported for a stud 2IOD compared to bar, ball and PEEK (polyether ether ketone) attachments in the presence of higher inter‐implant angulations (Aroso et al, ; Choi, Yun, Jeong, & Huh, ; Kurtulus & Gurbulak, ; Srinivasan et al, ; Sultana, Bartlett, & Suleiman, ). Fatigue tests, simulating 5 years of denture function, did not produce wear in the metal stud abutments (Aroso et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting investigation to juxtapose against the Hahnel et al 146 study was published by Choi et al 147 This research group performed an in vitro investigation to compare the retentive properties of an implant attachment system that incorporates a nylon insert (LOCATOR, Zest Anchor; Zest Dental Solutions) and an attachment with a polyetherketoneketone (PEKK) insert (CM LOC, Cendres+Metaux) on 2-implant mandibular overdentures during simulated masticatory loadings and insertion and removal cycles.…”
Section: Implant Removable Prosthodonticsmentioning
confidence: 99%